A Comparison of Granite Genesis in the Adelaide Fold Belt and Glenelg River Complex Using U–Pb, Hf and O Isotopes in Zircon. (11th October 2022) - Turner, Simon; Ireland, Trevor; Foden, John; Belousova, Elena; Wörner, Gerhard; Keeman, Jelte
Abstract: We present new U–Pb ages and Hf and O isotope data for zircon from I-, S- and A-type granites from both the western and eastern edges of the Delamerian Orogen in southeastern Australia. The I-type Tanunda Creek Gneiss contains zircon populations of 507 ± 4 and 492 ± 6 Ma inferred to reflect igneous and metamorphic ages, respectively. The I-type Palmer Granite yielded an age of 509 ± 3 Ma, and the Port Elliot S-type Granite has a magmatic age of 508 ± 7 Ma. Inherited zircon in these granites range from 1092 to 3343 Ma, probably derived from assimilation of Adelaide Group sediments. The Murray Bridge A-type Granite is 490 ± 2 Ma in age and lacks inherited zircon. In the Glenelg River Complex, an S-type migmatite from near Harrow contains a complex zircon population. It is most likely 500 Ma in age and has inherited zircon of 550–700, 1000–1100 and 2437 Ma, hence matching those from the Kanmantoo Group. From this and detrital zircon ages, we infer that only the Kanmantoo Group extends across the Murray Basin into the Glenelg River Complex. The Wando Tonalite and Loftus Creek I-type granites yielded ages of 501 ± 2 and 486 ± 3 Ma, respectively. Zircon from the Dergholm Granite has suffered Pb loss, and the best age estimate for this granite is 488 ± 5 Ma. Combining all the granite data together, εHft and δ 18 O in the magmatic zircon range from 5.6 to −10.3 and from 5.8 to 8.1, respectively, and are well correlated. The zircon indicates the same temporal and compositional evolution of granitic petrogenesis across 300 km of strike, reaffirming the notion that these terranes form part of the same orogen. Westward-directed subduction caused orogenic thickening, heating and increasing amounts of crustal contribution. This was followed by convective thinning of the thickened mantle lithosphere and a return to more primitive magmas lacking significant crustal contributions. It contrasts significantly with inferred granite petrogenesis and tectonic style in the younger Lachlan and New England Fold Belts further east that were not built upon extended cratonic lithosphere.